2014
DOI: 10.1104/pp.114.235390
|View full text |Cite
|
Sign up to set email alerts
|

Hypoosmotic Expression of Dunaliella bardawil ζ-Carotene Desaturase Is Attributed to a Hypoosmolarity-Responsive Element Different from Other Key Carotenogenic Genes    

Abstract: Some key carotenogenic genes (crts) in Dunaliella bardawil are regulated in response to salt stress partly due to salt-inducible cisacting elements in their promoters. Thus, we isolated and compared the z-carotene desaturase (Dbzds) promoter with other crts promoters including phytoene synthase (Dbpsy), phytoene desaturase (Dbpds), and lycopene b-cyclase1 (DblycB1) to identify salt-inducible element(s) in the Dbzds promoter. In silico analysis of the Dbzds promoter found several potential cis-acting elements, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
36
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(37 citation statements)
references
References 82 publications
(129 reference statements)
1
36
0
Order By: Relevance
“…There were several TATA and CAAT boxes that are typical in eukaryotic promoters, multiple light response elements (GATABOX, CGCGBOXAT and SORLIP1AT), ASF1MOTIFCAMV involved in abiotic and biotic stress, and SRE (GT1GMSCAM4). Previously, cis ‐acting elements of the promoters of Dbpsy (Lao et al ., ) and Dbzds (Lao et al ., ) have been analyzed (Table ). Dbpsy and Dblcyb promoters contained the same SRE, named GT1GMSCAM4.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…There were several TATA and CAAT boxes that are typical in eukaryotic promoters, multiple light response elements (GATABOX, CGCGBOXAT and SORLIP1AT), ASF1MOTIFCAMV involved in abiotic and biotic stress, and SRE (GT1GMSCAM4). Previously, cis ‐acting elements of the promoters of Dbpsy (Lao et al ., ) and Dbzds (Lao et al ., ) have been analyzed (Table ). Dbpsy and Dblcyb promoters contained the same SRE, named GT1GMSCAM4.…”
Section: Resultsmentioning
confidence: 99%
“…It was found that the transcription levsls of some carotenogenic genes in D. bardawil were up‐regulated under salt stress (Lao et al ., ). It was shown that the Dbpsy promoter contained a salt‐regulated element (SRE) and light‐regulated elements involved in stress‐responsive gene expression (Lao et al ., ), and the Dbzds promoter had a hypoosmolarity‐responsive element (HRE) instead of salt‐inducible elements (Lao et al ., ).…”
Section: Introductionmentioning
confidence: 97%
See 2 more Smart Citations
“…The nature of the environmental and developmental stimuli that alter apocarotenoid formation may in some cases also reflect the ecological roles of apocarotenoids (e.g., as pollinator attractants). Examples of stimuli that affect apocarotenoid formation are summarized in Table I. Environmental and developmental stimuli also alter the expression of many carotenoid biosynthetic genes, altering carotenoid composition, which may in turn promote production of specific apocarotenoids [101][102][103]. However, the relationship between carotenoid and apocarotenoid levels is not always straightforward as expression and localization of substrates and enzymes will affect apocarotenoid production.…”
Section: Box 1 Environmental and Developmental Stimuli Regulate Apocmentioning
confidence: 99%